Fossils distribution from Garagu Formation (Early Cretaceous), diversity and Paleoennvironmental conditions, Kurdistan Region, North Iraq - Ghafor, Imad Mahmood; M.J.Mohialdeen, Ibrahim (Sulaimani Journal for Pure and Applied Sciences, 2016)
The most recent studies reformed the occurrence of Garagu Formation, Dohuk area, Kurdistan Region, Northeastern Iraq. The present paleontological study, in the type locality, aids the recognition of the formation. Recognizing fourty nine genera and species of the; Benthonic and Planktonic Foraminifera, Ostracods, Calcareous Algae, and Coral, with other fossils such as ; Gastropoda shell, Echinodermata spine, Pelecypoda shell, Spone spicules and Brachiopds shell, which are described and figured. The stratigraphic distribution and diversity of these fossils assemblages indicate the Hauterivian-Barremian age of the Garagu Formation. The fossil assemblages in the Garagu Formation are characteristic for a shallow marine setting with local transitions to continental facies, shelf lagoonal environment and open platform.
Keywords: Garagu FormationMicrofossilsPaleoenvironmentDohukKurdistanIraq